(untitled) (European Journal of Pure and Applied Mathematics, 2024)
The basic objective of this research work is to introduce and investigate the properties of micro pre-frontier, micro pre-exterior, micro pre-border, micro pre-kernel using the concept of frontier, exterior, border and kernel.